Religiosidade à brasileira no drama de Nelson Rodrigues - Souto, Petra Ramalho (2015)
The research, Religiosity in the Brazilian drama of Nelson Rodrigues, deals with the study of representations of religious miscegenation in Nelson Rodrigues’ drama. Therefore, we choose as objects reading texts “The seven kittens”, “The deceased” and “The serpent”, respectively written in 1958, 1953 and 1978. To understand the chosen subject, the phenomenon of religious miscegenation in Brazil, we rely on anthropological view of Hélène Clastres, French scholar of religious manifestations of Brazilian Indians and in view of Darcy Ribeiro, a national anthropologist and novelist. To these studies, we combined the research of Eneida Leal on deities in Brazil and the philosophical postulates of the Italian philosopher, Nicola Abbagnano. Regarding the understanding of Nelson Rodrigues work we report, notably, the study proceeded by Sabato Magaldi, in addition to research Decio de Almeida Prado and Roberto Farias. As for the theoretical and methodological apparatus, used in the Georg Lukacs perspective, endorsed, in Brazil, Antonio Candido and the scholar of national drama, Decio de Almeida Prado. In these ways and understandings, we paided attention to the rodriguian’s particularities the settings of our devotions.